Exploring the political economy of everyday life on the Costa Rican frontier from agrarian reform to the pineapple boom - Shaver, Irene (2014)
Tesis (Ph. D.) -- CATIE. Escuela de Posgrado. Turrialba (Costa Rica), 2014